Genghis Khan and the making of the modern world - Weatherford, Jack (New York Broadway Books, 2004)
Weatherford's lively analysis restores the Mongol's reputation, and it takes wonderful learned detours.... Well written and full of suprises.
Keywords: Mongols--Kings and rulers; Biography-Historical